Tactics And Methodology For Interrogating Persons In Relation To State Or Hiv Disease/Aids Communication Crime - Kurambaev Takhir Khosinbaevich (Euro Asian Journal Publishing, 2024)
The article covers the questioning of victims, suspects, and witnesses of sexually transmitted or HIV/AIDS crimes. Because there are specific aspects of questioning them. Therefore, tactics and methods of interrogation of individuals are revealed. Also, some errors and shortcomings in the investigative practice related to the conduct of this investigative action, as well as justified proposals and recommendations for their elimination, were developed
Keywords: sexual intercourse; HIV; AIDS; witness